Konsep Pendidikan Iman dalam QS. Al-Mukminun - Dadan Rusmana; Yayan Rahtikawati; Mohamad Akbar Nugraha; Muhammad Zia Alkhair; Siham Adzan Al-Mujaddid (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
This paper discusses the concept of faith education in QS. Al-Mukminun, the focus of the study in this paper is the search for the concept of faith education contained in the QS. Al-Mu'minun. The writing method applied in this writing is the maudhu`i (thematic) interpretation method, by analyzing the verses of the Koran contained in the QS. Al-Mu'minun to find the concept of faith education contained in it. The steps of the maudhu`i interpretation method formulated by Abdul Hay Al-Farmawi. In this formulation there are seven steps in the maudhui interpretation, namely starting with determining the theme, and collecting verses related to the theme, then sorting the verses based on their historical context, then understanding the munasabah of the verses related to other verses, and compiling a perfect discussion framework, and completing discussion through quotations of related hadith, and the last step is to examine the related verses as a whole to find one concept that is studied. The data source in this article is the Koran and several secondary sources, such as the book Al-Mu'jam al-Mufahras li alfaadzi Al Qur'an by Muhammad Fuad Al-Baqi, several books and articles. This paper is a library research using a qualitative approach, which is trying to describe a variable, symptom or condition "as is", and is not intended to test certain hypotheses. The result of this paper is to find the concept of faith education contained in QS. Al-Mu'minun.